Algebraic Techniques 01 - Perfect Square and Quadratic Equation

For 1x<21 \leq x < 2, simplify the following expression.

1x+2x1+1x2x1\begin{aligned} \frac{1}{\sqrt{x + 2 \sqrt{x - 1}}} + \frac{1}{\sqrt{x - 2 \sqrt{x - 1}}} \end{aligned}

[Solution] Check the denominators if they can changed to the perfect square form. x+2x1=x1+2x1+1=(x1+1)2x2x1=x12x1+1=(x11)2\begin{aligned} x + 2 \sqrt{x - 1} &= x - 1 + 2 \sqrt{x - 1} + 1 = (\sqrt{x - 1} + 1)^2 \\ x - 2 \sqrt{x - 1} &= x - 1 - 2 \sqrt{x - 1} + 1 = (\sqrt{x - 1} - 1)^2 \end{aligned}

Since x<2x < 2, 1x+2x1+1x2x1=1x1+1+1x11=1x1+1+1x11=2(x1)1=22x\begin{aligned} \frac{1}{\sqrt{x + 2 \sqrt{x - 1}}} + \frac{1}{\sqrt{x - 2 \sqrt{x - 1}}} &= \frac{1}{|\sqrt{x - 1} + 1|} + \frac{1}{|\sqrt{x - 1} - 1|} \\ &= \frac{1}{\sqrt{x - 1} + 1} + \frac{-1}{\sqrt{x - 1} - 1} \\ &= \frac{-2}{(x - 1) - 1} \\ &= \frac{2}{2 - x} \end{aligned}

Solve the following equation.

x497x3+2012x297x+1=0\begin{aligned} x^4 - 97x^3 + 2012x^2 - 97x + 1 = 0 \end{aligned}

[Solution] The big feature of this equation is that the coefficients are symmetric. As divided by x2x^2, x297x+201297x+1x2=0\begin{aligned} x^2 - 97x + 2012 - \frac{97}{x} + \frac{1}{x^2} = 0 \end{aligned}

To make the perfect form, this can be rewritten to (x+1x)297(x+1x)+2010=0\begin{aligned} \left(x + \frac{1}{x}\right)^2 - 97\left(x + \frac{1}{x}\right) + 2010 = 0 \end{aligned}

Assuming that y=x+1/xy = x + 1/x, y297y+2010=0(y30)(y67)=0\begin{aligned} y^2 - 97y + 2010 = 0 \\ (y - 30)(y - 67) = 0 \end{aligned}

So y=x+1/x=30,67y = x + 1/x = 30, 67, x230x+1=0,x=15±224x267x+1=0,x=67±44852\begin{aligned} x^2 - 30x + 1 &= 0, \quad x = 15 \pm \sqrt{224} \\ x^2 - 67x + 1 &= 0, \quad x = \frac{67 \pm \sqrt{4485}}{2} \end{aligned}

For real numbers xx and yy, prove that

3(x+y+1)2+13xy\begin{aligned} 3(x + y + 1)^2 + 1 \geq 3xy \end{aligned}

[Solution] Aussuming that x+y=ax + y = a and xy=bxy = b, 3(a+1)2+13b\begin{aligned} 3(a + 1)^2 + 1 \geq 3b \end{aligned}

Considering the quadratic equation t2at+b=0t^2 - at + b = 0 whose two real roots are xx and yy, its discriminant Δ=a24b0\Delta = a^2 - 4b \geq 0, which is ba2/4b \leq a^2 / 4. Therefore, the problem can be proved by showing that the following inequality holds. 3(a+1)2+13a249a2+24a+160,(3a+4)20\begin{aligned} 3(a + 1)^2 + 1 &\geq \frac{3a^2}{4} \\ 9a^2 + 24a + 16 \geq 0, &\quad (3a + 4)^2 \geq 0 \end{aligned}

Find real solutions of the following equation.

x4+16x12=0\begin{aligned} x^4 + 16x - 12 = 0 \end{aligned}

[Solution] By observation, this equation has no cubic and quadratic terms. So this can be represented as x4+16x12=(x2+a)2(bx+c)2=x4+(2ab2)x22bcx+a2c2\begin{aligned} x^4 + 16x - 12 &= \color{crimson}{(x^2 + a)^2 - (bx + c)^2} \\ &= x^4 + (2a - b^2)x^2 - 2bcx + a^2 - c^2 \end{aligned}

Comparing coefficients, 2a=b22a = b^2, 16=2bc16 = -2bc, and a2c2=12a^2 - c^2 = -12. Since a=b2/2a = b^2 / 2 and c=8/bc = -8/b, a2c2=12b2464b2=12\begin{aligned} a^2 - c^2 = -12 \Longleftrightarrow \frac{b^2}{4} - \frac{64}{b^2} = -12 \end{aligned}

So bb can be set to 22, and this makes that a=2a = 2 and c=4c = -4. x4+16x12=(x2+2)2(2x4)2=(x2+2x2)(x22x+6)=0\begin{aligned} x^4 + 16x - 12 &= (x^2 + 2)^2 - (2x - 4)^2 \\ &= (x^2 + 2x - 2)(x^2 - 2x + 6) = 0 \end{aligned}

Therefore, x2+2x2=0x^2 + 2x - 2 = 0 has solutions, x=1±3x = -1 \pm \sqrt{3}, and x22x+6=(x1)2+5=0x^2 - 2x + 6 = (x - 1)^2 + 5 = 0 has no solutions.

Given the following inequality for all real numbers x1x_1, x2x_2, \cdots, xnx_n, find all positive integers nn where n>1n > 1.

x12+x22++xn2xn(x1+x2++xn1)\begin{aligned} x_1^2 + x_2^2 + \cdots + x_n^2 \geq x_n (x_1 + x_2 + \cdots + x_{n - 1}) \end{aligned}

[Solution] This inequality can be rewritten as x12x1xn+x22x2xn++xn12xn1xn+xn20\begin{aligned} x_1^2 - x_1 x_n + x_2^2 - x_2 x_n + \cdots + x_{n - 1}^2 - x_{n - 1} x_n + x_n^2 \geq 0 \end{aligned}

By using some proper perfect square, (x1xn2)2++(xn1xn2)2n14xn2+xn20(x1xn2)2++(xn1xn2)2n54xn2\begin{aligned} &\left( x_1 - \frac{x_n}{2} \right)^2 + \cdots + \left( x_{n - 1} - \frac{x_n}{2} \right)^2 - \frac{n - 1}{4} x_n^2 + x_n^2 \geq 0 \\ &\Longleftrightarrow \left( x_1 - \frac{x_n}{2} \right)^2 + \cdots + \left( x_{n - 1} - \frac{x_n}{2} \right)^2 \geq \frac{n - 5}{4} x_n^2 \end{aligned}

If n5n \leq 5, the inequality holds. If n>5n > 5, it does not hold when x1=xn/2x_1 = x_n / 2, \cdots, xn1=xn/2x_{n - 1} = x_n / 2, xn=1x_n = 1. Therefore, the solutions are n=2,3,4,5n = 2, 3, 4, 5.

Reference

[1] Titu Andreescu, 105 Algebra Problems.


© 2024. All rights reserved.